The Effect of Heating of B20 Fuel to Combustion Characteristic on the Diesel Engine Based on Experiment - Semin Semin; Beny Cahyono; Faris Mishbahul Muhammad; Barokah Barokah (International Journal of Marine Engineering Innovation and Research, 2020)
According to Bank Indonesia, the current account deficit of Indonesia. In the second quarter of 2018 increased to USD 8.0 billion. One of the government's programs to reduce the current account deficit is by implementing a B20 biodiesel policy. The increasing percentage of biodiesel in fuel blends tends to decrease the quality of spray atomization, where it indicated by longer droplet breakup, spray penetration, droplet lifetime, and bigger droplet diameter. Higher viscosity causes a decrease in the quality of the spray from the injector. Previous research shows that the inlet temperature of the fuel can make the performance of small diesel engines slightly better. The research was conducted using petrodiesel and biodiesel fuel by varying inlet temperature of 50oC and 70oC. Based on that this research is conducted to understand the effect of fuel heating diesel engine combustion process. The result shows that generally maximum pressure is increased for every increase in fuel temperature. The heat release shows a decreasing trend for every increase in fuel temperature. Knock detection shows that generally when the fuel temperature increased the knocking is also increased. The increasing fuel temperature shows little effect on ignition delay except for the higher temperature of 60oC and 70oC where the ignition delay is the lowest and closest to that of a dexlite fuel.